Effects of Thrombospondin-1 (THBS1) and Toll-like Receptor 4 (TLR-4) levels in the serum and synovial fluid of patients with knee osteoarthritis: THBS1 and TLR-4 levels in knee osteoarthritis - Xu, Yingjie; Tian, Zhen; Liang, Mingjin; Li, Xiaoyun (Journal of Medical Biochemistry, 2025)
Objective To explore the changes in and significance of Thrombospondin-1 (THBS1) and Toll-like receptor 4 (TLR-4) levels in the serum and joint fluid of patients with knee osteoarthritis (KOA). Methods 184 KOA patients who were admitted to our hospital between May 2022 and February 2025 were chosen to serve as the observation group, and another 64 healthy adults who underwent physical examinations at the same hospital during the same period composed the control group. Tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, THBS1, and TLR-4 levels in the two groups’ serum and joint fluid were compared. The correlations between the levels of TNF-α, IL-1β, THBS1 and TLR-4 in the serum and synovial fluid of the two groups and the severity of KOA were evaluated, and the clinical value of THBS1 and TLR-4 in the diagnosis of KOA was analyzed. Results TNF-α, IL-1β, THBS1, and TLR-4 levels in the observation group’s serum and joint fluid were considerably higher than those in the control group (P<0.05). With an increase in Kellgren-Lawrence (K-L) grade, the observation group’s serum and joint fluid had higher amounts of TNF-α, IL-1β, THBS1, and TLR-4. When TNF-α, IL-1β, THBS1, and TLR-4 levels were compared among K-L grades, statistically significant differences were found (P<0.05). The K-L grade of the patients was positively correlated with TNF-α, IL-1β, THBS1, and TLR-4 in the blood and joint fluid (P<0.05), and the factors of TNF-α, IL-1β, THBS1, and TLR-4 in the observation group’s serum and joint fluid were positively correlated with each other (P<0.05). The sensitivity and specificity of serum THBS1 and TLR-4 for the diagnosis of KOA were 0.916 and 0.889 and 0.825 and 0.865, respectively, and the optimal cutoff values were 247.262 and 5.084 ng/mL, respectively. The sensitivity and specificity of THBS1 and TLR-4 in the joint fluid for diagnosing KOA were 0.945 and 0.932 and 0.985 and 0.916, respectively, and the optimal cutoff values were 239.745 and 4.620 ng/mL, respectively. Conclusion THBS1 and TLR-4 in serum and synovial fluid can be used as potential markers for the clinical diagnosis and assessment of KOA conditions, both of which have high diagnostic efficacy. Moreover, the detection of serum THBS1 and TLR-4 is less invasive, has a lower cost, and is more acceptable to patients.